Acute type A dissection, coarctation of aorta, and levoatriocardinal vein—A rare combination. Issue 10 (23rd July 2021) - Patel, Kartik; Patel, Archit; Ananthanarayanan, Chandrasekaran
Abstract: Concomitant presence of acute type A dissection, coarctation of aorta and levoatriocardinal vein has not been described. We here present a case of aortic anuerysm complicated by type A dissection with coarctation of aorta and levoatriocardinal vein.